Health Technologies for Detecting High Risk Conditions in Pregnancy: A Systematic Review - Devita Madiuw; Restuning Widiasih; Pipih Napisah (Universitas Padjadjaran, 2019)
In this technological era, various health technology including media, instruments and tools are created in area maternal and babies’ health. However, comprehensive information about these technology products are limited. This literature review aimed to find health technology in area maternal and baby especially in detecting high risk conditions in pregnancy. Method, this is a systematic review, the articles were searched from two databases including PubMed and CINAHL using several keywords. The keywords were high risk, pregnant women and technology OR instrument OR tools. Inclusion criteria are primary research, English language, and publications in the last 5 years. After the critical appraisal, a total of 16 articles included in the analysis. Result: The literature related of technology divided into two criteria which are the questionnaire development and health tools or devices. None of technology came from Indonesia. The entire technology showed effectiveness in detecting risks, and interventions to improve prenatal care. The target user for health tools mostly health professionals. Conclusion: various health technologies in area maternal in baby health are identified, however the majority of them provided from health professionals. Technology development is needed specifically, in the form of simple and practical tools or devices to assess foetal health with target user is pregnant women with high risk pregnancy.